Bonjour j'aurai besoin d'aide pour un devoir : Développer puis réduire si possible cette expression : A : 4x + (2x + 1) (5x - 3) B :( x + 3) (y + 9) +10x -7 C : (3x - 5) (7 + 6x) - (7 + x) D : 5x + 1 -(x + 4 ) (x - 9 )

1

Réponses

Meilleure réponse !
2012-11-07T15:43:18+01:00

A=  4x + (2x + 1) (5x - 3) = 4x + 10x^2 - 6x + 5x - 3 = 10x^2 +3x - 3
B = ( x + 3) (y + 9) +10x -7 = xy + 9x + 3y + 27 +10x -7 = xy + 19x + 3y -7

C =  (3x - 5) (7 + 6x) - (7 + x) = 21x + 18x^2 - 35 -30x - 7 + x = 18x^2 - 8 - 44
D = 5x + 1 -(x + 4 ) (x - 9 ) = 5x + 1 -(x^2 - 9x + 4x - 36)= 5x + 1 -x^2 + 9x - 4x + 36= - x^2 + 10x + 36